p ( x ) is a monic polynomial of degree 4, such that
p ( 2 ) p ( 3 ) p ( 4 ) p ( 5 ) = − 5 5 = − 1 8 1 = − 3 7 7 = − 6 1 9 .
Then what is the value of p ( ω ) ?
Details and Assumptions
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice approach SG
Same solution!!
But what if it is not given that polynomial is monic.
Let p ( x ) = x 4 + a x 3 + b x 2 + c x + d
Substituting 2 , 3 , 4 and 5 into x , we obtain four simultaneous equations.
Solving them yields a = − 1 0 , b = 0 , c = − 1 and d = 1 1
Hence,
f ( ω ) = ω 4 − 1 0 ω 3 − ω + 1 1
= ω − 1 0 − ω + 1 1
= 1
Perfect way to solve the problem.
Let
p
(
x
)
=
x
4
+
b
x
3
+
c
x
2
+
d
x
+
e
.
p
(
2
)
=
1
6
+
8
b
+
4
c
+
2
d
+
e
.
p
(
3
)
=
8
1
+
2
7
b
+
9
c
+
3
d
+
e
.
p
(
4
)
=
2
5
6
+
6
4
b
+
1
6
c
+
4
d
+
e
.
p
(
5
)
=
6
2
5
+
1
2
5
b
+
2
5
c
+
5
d
+
e
.
By solving these equations, we will get
b
=
−
1
0
,
c
=
0
,
d
=
−
1
and
e
=
1
1
.
Hence,
p
(
x
)
=
x
4
−
1
0
x
3
−
x
+
1
1
.
p
(
ω
)
=
ω
4
−
1
0
ω
3
−
ω
+
1
1
=
ω
−
1
0
+
ω
+
1
1
=
1
.
nice solution
Add (1, 1) to (2, -55), (3, -181), (4, -377) and (5, -619) to form a monic polynomial of degree 4, p(x) = x^4 - 10 x^3 - x+ 11, by Cramer's 5 x 5 determinants.
x^3 - 1 = (x - 1)(x^2 + x + 1) for omega, w = -1/ 2 + j Sqrt (3)/ 2,
w^4 = w <=> w^4 - w = 0, while w^3 = 1,
p (w) = w^4 - 10 w^3 - w + 11 = - 10 + 11 = 1
Note:
D = 288
D 1 = 288
D p = -2880
D q = 0
D r = -288
D s = 3168
Problem Loading...
Note Loading...
Set Loading...
ω represents cube root of unity. Why not we let, for the sake of solving the problem in a simple manner, that cube root be 1 itself?
The problem thus becomes much simpler. We just need to find p ( 1 ) , being given p ( 2 ) , p ( 3 ) , p ( 4 ) , and p ( 5 ) .
We can straightforwardly apply the Method Of Differences .
We make the difference table as follows:-
n 1 2 3 4 5 f ( n ) 1 − 5 5 − 1 8 1 − 3 7 7 − 6 1 9 D 1 ( n ) − 5 6 − 1 2 6 − 1 9 6 − 2 4 2 D 2 ( n ) − 7 0 − 7 0 − 4 6 D 3 ( n ) 0 2 4 D 4 ( n ) 2 4
We hereby use the fact that being the polynomial quartic, the 4 t h difference will be constant, and will be equal to 4 ! = 2 4 times the leading coefficient, being 1 .